ОБРАЗ ФЕИ В ЛЕГЕНДАХ И ИХ ИСТОРИЧЕСКИЕ ОСНОВЫ - Калбаева, Г.С. (SCIENCE and SOCIETY, 2023)
The article deals with the artistic role of fairy image in the epical interpretation and its social and historical backgrounds.Ways of artistic perfection in the result of mythological evolution are revealed.
Keywords: image; mythological belief; cult of nature; cult of women; mythological personage; historical data; literary image